Primary Health Centres and Patients Satisfaction Level in Haripad Community Development Block of Kerala, India - Sarath Chandran and Pankaj Roy (international Journal of Current Research, 2014)
The main objectives of the present study were to show the spatial distribution of Primary Health Centres in the Haripad Block of Kerala and to investigate the patients’ perception regarding the services provided by the Primary Health Centres. Spatial distribution distr ibution of Primary Health Centres was shown with the help of GIS mapping. Out of eight Primary Health Centres of the Block, five of them were selected by lottery method of simple random sampling for the present study. A pre designed schedule was used for the t he generation of primary data. The collected information was compiled, tabulated and analysed by using standard statistical methods. The main factors affecting the utilization of primary health care services in Haripad Block lock were easy accessibility, availa availability of medicine etc. The major problems of all sampled Primary Health Centres were the less number of doctors, absence of doctors from services, the lack of sanitary facilities and other infrastructure such as inpatients room, lab, bed etc.